Midgut volvulus: a rare cause of acute intestinal obstruction in adults - Jain, Rahul; Gupta, Sunita; Neogi, Sushanto; Mittal, Ankul (International Surgery Journal, 2017)
Malrotation with volvulus of midgut bowel loop, a developmental anomaly of intestinal fixation, occurs due to failure of rotation of proximal midgut around the mesenteric vessels during the second stage of rotation. Anomalies presenting in adults is very rare and incidence reported is 0.0001% to 0.19%. We report a case of a young female with acute on chronic presentation of midgut malrotation.